2017
DOI: 10.1016/j.antiviral.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol administration increases the efficacy of oseltamivir for the treatment of mice infected with influenza viruses

Abstract: Oseltamivir is an influenza neuraminidase inhibitor that along with supportive therapy has shown to help critically ill patients infected with H7N9 and H1N1pdm influenza virus strains to recover from disease. The standard of care recommends the administration of oseltamivir via oral route which represents difficulties in patients with gastrointestinal complications. Here we tested the use of aerosol administration of oseltamivir to treat mice infected with influenza A/H7N9 virus or influenza A/H1N1pdm virus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Our results are congruent with other reports showing that oral oseltamivir delivery is less efficacious than aerosolized oseltamivir. Notably, Leyva-Grado and colleagues compared several routes of administration of oseltamivir, and found that aerosolized oseltamivir given 24 h after infection confers protection against several strains of influenza, while oral oseltamivir protection was strain-specific and achieved at high doses only (Leyva-Grado 2017). Other reports indicate that oral oseltamivir may be efficacious at lower viral titers (Marjuki 2014) for extended treatment periods (Byrn 2015, Smee 2016,).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are congruent with other reports showing that oral oseltamivir delivery is less efficacious than aerosolized oseltamivir. Notably, Leyva-Grado and colleagues compared several routes of administration of oseltamivir, and found that aerosolized oseltamivir given 24 h after infection confers protection against several strains of influenza, while oral oseltamivir protection was strain-specific and achieved at high doses only (Leyva-Grado 2017). Other reports indicate that oral oseltamivir may be efficacious at lower viral titers (Marjuki 2014) for extended treatment periods (Byrn 2015, Smee 2016,).…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir) that block viral egress to potentially ameliorate disease are currently in use. Despite considerable efficacy in murine models in lowering viral titers and improving disease outcome [143,144], its protective effect in humans is controversial and limited benefit has been shown in the majority of patients [145,146]. Additionally, highly resistant strains of IAV to Oseltamivir have recently emerged that raises growing concern [147].…”
Section: Targeting Cell Death Programs As a Potential Therapy?mentioning
confidence: 99%
“…Oseltamivir como profilaxia da gripe [50], [51]. A nitazoxanida é relatada, na literatura, como um novo candidato a fármaco para o tratamento do coronavírus da síndrome respiratória do Oriente Médio [52].…”
Section: Histogramas Dos Nebulizadoresunclassified